Effect of Using English Song on Students’ Vocabulary Mastery at 7th Grade of MTS Private Al Azhar Education Foundation Medan - Noor Muhammad Salim; Zulfitri (Medan Resource Center, 2023)
Four skills in teaching English, that we always learn are reading, listening, speaking, and writing. There are several elements of language which support these four skills are structure, vocabulary, pronunciation and spelling. Vocabulary is one of the most significant things to be learned in the language, and it is the main center of learning a foreign language. Anggraini (2013:2) states that in teaching English, teaching vocabulary is an essential activity since vocabulary mastery applied to all language learning and concern all or any four language skills such learning, speaking, reading and writing. Learning vocabulary is significant because the student’s ability to learn how to write and read English, as well as to proposing their ideas and knowing the subject, vocabulary mastery is decided. If the students lack vocabulary, they will have trouble communicating and transmitting message. It is also difficult for students with limited vocabulary to understand the oral and written language because vocabulary is a central component of learning English.